2011
DOI: 10.1111/j.1530-0277.2011.01632.x
|View full text |Cite
|
Sign up to set email alerts
|

Randomized Controlled Trial of Mailed Personalized Feedback for Problem Drinkers in the Emergency Department: The Short‐Term Impact

Abstract: Mailed personalized feedback is efficacious in reducing quantity/frequency of alcohol consumption among patients with alcohol-involved ED presentations. Mailed feedback has high cost-efficacy and a low absolute cost, making it a promising candidate for integration into ED care.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
47
3

Year Published

2012
2012
2019
2019

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 20 publications
(51 citation statements)
references
References 65 publications
1
47
3
Order By: Relevance
“…An ultra‐BI intervention was present in six studies with a face‐to‐face interaction of 10 min or less, three with a computer intervention, two with a mobile phone intervention and two that provided a pamphlet only . Eleven studies assessed change in quantity of alcohol consumed, and one study assessed change in frequency of alcohol use.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…An ultra‐BI intervention was present in six studies with a face‐to‐face interaction of 10 min or less, three with a computer intervention, two with a mobile phone intervention and two that provided a pamphlet only . Eleven studies assessed change in quantity of alcohol consumed, and one study assessed change in frequency of alcohol use.…”
Section: Resultsmentioning
confidence: 99%
“…Of the 13 included studies, one was described as a pilot and five lacked sufficient power to show an effect because of small sample size or large loss to follow up, which ranged from 20% to 50% …”
Section: Resultsmentioning
confidence: 99%
“…Driving under the influence of alcohol or might be associated with alcohol dependence [41]. A review of studies on of interventions to reduce alcohol problems among ED- patients, found that interventions reduced alcohol related injuries [42]. Such interventions might be effective if they were offered to alcohol positive injured drivers.…”
Section: Discussionmentioning
confidence: 99%
“…As with the pharmacist- and GP-based SBI, this screening used the AUDIT questionnaire to screen all patients who presented to a participating ED. Personalised feedback was subsequently mailed to participants by the research team, providing them with information about their level of drinking, relative to other people in their community, and with advice on low-risk levels of alcohol consumption [30].…”
Section: Methodsmentioning
confidence: 99%